Health, environment, current knowledge of the heads of household and acute respiratory infection in toddlers - Martina Bedho; Rif'atunnisa Rif'atunnisa; Khrispina Owa; Try Ayu Patmawati (Malahayati International Journal of Nursing and Health Science, 2023)
Background: The ten patrons of disease at the Moni Health Center, the highest acute respiratory infection (ARI) of all cases, the second highest ARI in toddlers (62.90%) in Ende District. ARI can inhibit oxygenation of the body, causing decreased cell metabolism, thereby inhibiting growth and development, can contribute to morbidity and mortality in infants. Toddlers are still fully cared for by the family, which is the front line to prevent toddlers from getting sick.Purpose: Determine the effect of knowledge and family home environment on the incidence of respiratory infections in toddlers.Method: The research design is a mix of methods and approaches cross sectional. The sample size was calculated based on the Slovin formula of 164 respondents. Sampling using purposive dan accidental sampling. Data collected by interview, observation. The instrument used is the standard instrument. Bivariate Analysis Who Square to examine the effect of family tasks on the incidence of ARI. Logistic regression test to analyze the strength of the influence of knowledge and family home environment on the incidence of ARI at the 95% confidence level and significance limit p ≤0,05.Results: Bivariate test increases the risk, namely family knowledge OR=1.950 (95% CI: 1.571-2.421; p=0.000), maintenance of the home environment, OR = 94.53 (95%) CI: 4.120 - 21.690p - value = 0.000 ), In the multivariate analysis, it was found that the most dominant variable influencing increased risk was the maintenance of the home environment. There is a need for periodic health counseling and promotion related to efforts to prevent and control ARI, further research needs to use other methods.Conclusion: The most dominant variable that influences increasing risk is the maintenance of the home environment.  There is a need for periodic health counseling and promotion related to efforts to prevent and control respiratory  infections, further research needs to use other methods.